Malaria vaccine candidate antigen targeting the pre‐erythrocytic stage of Plasmodium falciparum produced at high level in plants. Issue 11 (10th October 2014) - Voepel, Nadja; Boes, Alexander; Edgue, Güven; Beiss, Veronique; Kapelski, Stephanie; Reimann, Andreas; Schillberg, Stefan; Pradel, Gabriele; Fendel, Rolf; Scheuermayer, Matthias; Spiegel, Holger; Fischer, Rainer
Abstract Plants have emerged as low‐cost production platforms suitable for vaccines targeting poverty‐related diseases. Besides functional efficacy, the stability, yield, and purification process determine the production costs of a vaccine and thereby the feasibility of plant‐based production. We describe high‐level plant production and functional characterization of a malaria vaccine candidate targeting the pre‐erythrocytic stage of Plasmodium falciparum. CCT, a fusion protein composed of three sporozoite antigens (P. falciparum cell traversal protein for ookinetes and sporozoites [PfCelTOS], P. falciparum circumsporozoite protein [PfCSP], and P. falciparum thrombospondin‐related adhesive protein [PfTRAP]), was transiently expressed by agroinfiltration in Nicotiana benthamiana leaves, accumulated to levels up to 2 mg/g fresh leaf weight (FLW), was thermostable up to 80°C and could be purified to >95% using a simple two‐step procedure. Reactivity of sera from malaria semi‐immune donors indicated the immunogenic conformation of the purified fusion protein consisting of PfCelTOS, PfCSP_TSR, PfTRAP_TSR domains (CCT) protein. Total IgG from the CCT‐specific mouse immune sera specifically recognized P. falciparum sporozoites in immunofluorescence assays and induced up to 35% inhibition in hepatocyte invasion assays. Featuring domains from three promising sporozoite antigens with different roles (attachment and cell traversal) in the hepatocyte invasion process, CCT has the potential to elicit broader immune responses against the pre‐erythrocytic stage of P. falciparum and represents an interesting new candidate, also as a component of multi‐stage, multi‐subunit malaria vaccine cocktails.